The Evaluation of the use of Antihypertensive Drugs with ATC&DDD Method in Cardiac Poly Geriatric Patient at Ajibarang Hospitas Inpatient Instalation - Khumaeni, Eko Hidayaturrohman; Mildawati, Ratna; Prasetyawan, Fendy (International Journal of Contemporary Sciences (IJCS), 2023)
Hypertension is one of the leading causes of mortality and morbidity in Indonesia. This research aims to determine the quantity of antihypertensive drugs used with Anatomical Therapeutic Chemical & Defined Daily Dose methods and determine antihypertensive drugs which include in Drug Utilization 90% segment. This research used secondary data which were taken from the patient's Medical Record. This research was quantitative descriptive research, the data were collected retrospectively. Data of antihypertensive drugs utilization and inpatient visit obtained from Medical Record Installation. Entire data then were processed to determine the quantity of antihypertensive drugs utilization in DDD/100 unit of inpatient day and Drug Utilization profile (DU90%).The results showed that the antihypertensive drugs utilization in hypertensive patients in RSUD Ajibarang were furosemid 28,07%, candesartan 17,42%, amlodipin 17,15%, spironolactone 11,52%, captopril 8,81%, valsaran 6,36%, irbesartan 3,60%, bisoprolol 3,38%, ramipril 3,31%, propranolol 0,34%. And from the DU90% table, drugs which include in the DU90% segment were furosemid, candesaran, amlodipin, spironolactone and captopril..